Optimizing Strategy for the Utilization of Shipping Channels and Management of Facilities at The Marunda Center Public Terminal, BUP PT. Pelabuhan Tegar Indonesia - Sigit Prayogo; Langas Denny Siahaan; Edi Abdurachman; Asep Suparman; Lira Agusinta (Dinasti Review, 2026)
This study aims to formulate strategies for optimizing the utilization of shipping channels and facility management at the Marunda Center Public Terminal operated by PT Pelabuhan Tegar Indonesia. The research addresses suboptimal channel use and terminal facility management that constrain vessel and cargo flow efficiency and reduce port competitiveness. A qualitative approach was applied through in-depth interviews with port management, operators, government agencies, and port users, complemented by Focus Group Discussions with key stakeholders. Thematic analysis was employed to identify core issues and strategic options. The findings reveal that limited channel depth and capacity, inadequate supporting infrastructure, and weak integration of inter-institutional information systems are the main constraints. The study recommends infrastructure upgrading, digital system integration, strengthened inter-agency coordination, and standardized operational procedures to improve efficiency, reduce service time, and reinforce Marunda Center Terminal’s role as a strategic logistics hub in the Greater Jakarta area.